1991
DOI: 10.1042/bj2740257
|View full text |Cite
|
Sign up to set email alerts
|

The pro-polypeptide of von Willebrand factor is required for the formation of a functional factor VIII-binding site on mature von Willebrand factor

Abstract: We have established that a recombinant von Willebrand Factor (vWF) mutant (vWFdelpro) that lacks the propolypeptide, in contrast with mature wild-type vWF, with which it is identical in terms of primary amino acid sequence, is not able to form a complex with Factor VIII. Wild-type vWF (flvWF) and vWFdelpro were expressed in AtT-20 cells. Under the culture conditions employed, completely processed multimerized flvWF and dimeric vWFdelpro were secreted into the medium. FlvWF and vWFdelpro were compared for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…In a later study, Bendetowicz et al (28) showed that the VWF variant that lacks the propeptide does bind FVIII, albeit with a reduced affinity. The apparent discrepancy between these studies has been attributed to the fact that the VWF variant that does not bind FVIII comprises an additional alanine before Ser-764 at its N terminus (28,35). Our study has shown that a native N terminus, which starts with Ser-764, is critical for FVIII binding.…”
Section: Journal Of Biological Chemistry 397mentioning
confidence: 43%
See 1 more Smart Citation
“…In a later study, Bendetowicz et al (28) showed that the VWF variant that lacks the propeptide does bind FVIII, albeit with a reduced affinity. The apparent discrepancy between these studies has been attributed to the fact that the VWF variant that does not bind FVIII comprises an additional alanine before Ser-764 at its N terminus (28,35). Our study has shown that a native N terminus, which starts with Ser-764, is critical for FVIII binding.…”
Section: Journal Of Biological Chemistry 397mentioning
confidence: 43%
“…It has been suggested that a VWF variant that lacks the propeptide does not bind to FVIII at all. As the propeptide mediates dimerization of the N-terminal side of VWF, it was proposed that proper dimerization is a prerequisite for effective FVIII binding (35). In a later study, Bendetowicz et al (28) showed that the VWF variant that lacks the propeptide does bind FVIII, albeit with a reduced affinity.…”
Section: Journal Of Biological Chemistry 397mentioning
confidence: 99%
“…Furthermore, a point riiutation at residue 91 has been reported in two patients with defective FVIIIhWF interaction [23,24]. Finally, it has been demonstrated that the propolypeptide of vWF is required for the formation of a functional FVIII-binding site on mature vWF [25]; this indicates that this FVIII binding property of vWF may be affected also by mutations located outside of the FVIIIbinding domain.…”
Section: Discussionmentioning
confidence: 95%
“…Recent evidence from animal experiments, upon administration of rvWF precursor molecules, suggests the presence of a mechanism for extracellular propeptide removal also (Turecek et al, in press). Despite the necessity of the propeptide for vWF multimerisation (Leyte et al, 1991;Wise et al, 1991), which in turn is believed to be essential for functional activity, its subsequent removal is mandatory to enable vWF to interact with factor VIII.…”
Section: Von Willebrand Factor Propeptide Removal By Full Length Furinmentioning
confidence: 99%